Levels of Adipokines in Ghanaian Women in Jamestown, Accra - Adjei, A.B. (University of Ghana, 2013)
Adipokines are bioactive mediators that communicate between adipose tissue and other biological systems. Adipokines have strongly been linked to adiposity and obesity. The body’s balance of adipokines is fundamental to prevent obesity and other non- communicable disease. However, their levels in the aetiogenesis of obesity or otherwise have not been studied in Ghana.. The aim of the study was to investigate the levels of plasma Leptin, Adiponectin, Resistin (major adipokines) among women between the ages of 20 to 80 years in James Town, Accra. One hundred and eleven women were used for this study using invitational sampling. A structured questionnaire covering subjects’ lifestyle and anthropometrics was administered to each consented subject. The subjects’ anthropometrics (weight, height, BMI, percentage body fat, visceral fat, skeletal muscle and resting metabolism) and blood pressure (BP) were taken. Total cholesterol (TC), high density lipoproteins cholesterol (HDL-c), low density lipoprotein cholesterol (LDL-c), triglycerides (TRIG), fasting blood glucose (FBG), Leptin, Adiponectin and Resistin were assessed. The prevalence of obesity in this study was 48% and body composition correlated with blood pressures of study subjects. Adiponectin levels correlated positively with LDL-c (r =0.219, p = 0.030), TCHOL/HDL-c (r=0.281, p = 0.005) and LDL/HDL (r = 0.269, p = 0.007). On the other hand, adiponectin correlated inversely with HDL-c (r = -0.226, p = 0.024). Adiponectin was high in normal subjects with normal SBP which supports other studies and therefore has the potential in protecting one from cardiovascular damage.
Thesis (MPHIL) - University of Ghana, 2013